Ad MENELUSURI JEJAK PERADABAN TEMBOK YERUSALEM DAN IMPLIKASINYA DALAM KONFLIK MODERN: JEJAK PERADABAN TEMBOK YERUSALEM - Karnu, Kosmas; Usman, Yosef (Sphatika: Jurnal Teologi, 2026)
The Jerusalem Wall, as one of the most iconic and sacred sites in the world, not only has historical and archaeological value, but also plays an important role in modern social and political dynamics. This article explores how the Jerusalem Wall reflects a rich civilization, including its influence on the cultural and religious identities of various communities. Through historical analysis, it reveals the long journey of these walls from ancient times to the present day, as well as how their changes reflect social and political changes in the region. The tensions surrounding these walls not only reflect religious and cultural differences, but also mirror the struggles of nationalism and political aspirations. With an interdisciplinary approach, this study invites readers to understand the complexity of the Jerusalem wall as a focal point of conflict, as well as a symbol of peace desired by many parties. Through this research, it is hoped that new perspectives will be found in understanding the relationship between cultural heritage, collective identity, and the dynamics of conflict in Jerusalem. Thus, the walls of Jerusalem are not merely physical structures, but also representations of the challenges and hopes faced by communities in this historically rich region.